2015
DOI: 10.1007/s00277-015-2348-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of paroxysmal nocturnal hemoglobinuria clones in response to immunosuppressive therapy of patients with severe aplastic anemia

Abstract: Whether paroxysmal nocturnal hemoglobinuria (PNH) clone in aplastic anemia (AA) is a prognostic factor to immunosuppressive therapy is a subject of debate. We evaluated hematological responses to immunosuppressive therapy (IST) in severe AA (SAA) patients with or without the presence of a PNH clone. In 97 SAA patients who received first-line IST between January and December 2011, 24 (24.7 %) had a PNH clone prior to treatment, with a median clone size of 7.82 % (range 1.19-45.46 %). The response rates to IST f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…In contrast, PNH testing for cases presenting with unexplained thrombosis in the absence of anemia or another cytopenia, as well as for patients diagnosed with other hematological/immunological disorders in the absence of a BM failure syndrome, emerged as worthless, with extremely low rates of PNH positivity. Overall, these results are in line with previous observations reported in the literature mostly in smaller patient series and specific diagnostic groups .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, PNH testing for cases presenting with unexplained thrombosis in the absence of anemia or another cytopenia, as well as for patients diagnosed with other hematological/immunological disorders in the absence of a BM failure syndrome, emerged as worthless, with extremely low rates of PNH positivity. Overall, these results are in line with previous observations reported in the literature mostly in smaller patient series and specific diagnostic groups .…”
Section: Discussionsupporting
confidence: 93%
“…These results emphasize the need for PNH testing in AA patients of any age, including also younger AA cases . In line with our observations, previous studies have shown that GPI‐deficient cells are frequently found in AA and MDS patients, while they are detected only in few MPN cases . Despite the exact frequency of PNH+ AA cases varies substantially in the literature (range 22% to 89%) , it is currently estimated to be ≈40% of cases , as also found in our series with slight differences according to the age of the patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the reliability of results obtained from minor PNH populations remains controversial. For example, several studies conducted on adults and/or children with AA reported that the presence of minor PNH populations was associated with a favorable response to IST [14,17,18,29,[31][32][33]. In contrast, a retrospective National Institutes of Health (NIH) study that included adults and children did not find differences between AA patients who did or did not respond to IST [10].…”
Section: Paroxysmal Nocturnal Hemoglobinuria (Pnh)mentioning
confidence: 84%
“…The utility of ARC in predicting IST outcomes has been confirmed in a proportion of reports, but not in others [12,[14][15][16][17]. Higher absolute neutrophil count (ANC) appears to be correlated with a better response rate of IST [15,18]; however, this result was not confirmed in Japanese and German children [12,19,20]. Further, the study of Japanese children demonstrated that lower white blood cell (WBC) count was indicative of a better response to IST rather than higher ANC [12].…”
Section: Pre-treatment Peripheral Blood Countsmentioning
confidence: 93%